Protocol for immunofluorescent staining, high-resolution imaging, and spatial projection of Schlemm’s canal in mouse whole-mount corneal limbus tissue - Weifa Wang; Peiyao Peng; Wenfo Hu; Xuyang Liu; Liming Yang; Rong Ju; Feng Zhang (STAR Protocols)
Summary: Schlemm’s canal (SC) is an endothelium-lined conduit with uniquely combined features of blood vessels and lymphatic vessels required for aqueous humor drainage from the eye. Here, we present a protocol for immunofluorescent staining of blood and lymphatic endothelial markers in mouse whole-mount anterior eye cup at different postnatal ages. We describe steps for tissue harvesting, fixation, antibody incubation, mounting, and high-resolution confocal microscopy. This protocol facilitates the understanding of SC formation and functionality at the cellular level.For complete details on the use and execution of this protocol, please refer to Gu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.